Analisis Pengembangan Obyek Wisata Terhadap Pendapatan Masyarakat (Studi Pada Pengembangan Obyek Wisata Kampung Warna-Warni Di Desa Janju Kecamatan Tanah Grogot Kabupaten Paser) - Sindita Nadya Indriani; Noor Rahmini (PPJP ULM, 2019)
The purpose of this study was to analyze the development strategy of Janju Village Colorful Village attractions in increasing people's income. This research method uses descriptive quantitative. While the technique for analyzing data is a SWOT analysis. The tourism development strategies obtained are: (1) Improving the quality of barcode scanners by utilizing the location of strategic tourism objects and the use of information technology. (2) Increasing the presence of tourism conscious groups by utilizing strategic locations. (3) The government supports increasing tourism promotion for tourism development. Tourism activities give direct results or indirect results for the surrounding community in the Colorful Village attractions, namely: (1) for the community will open jobs. (2) for the community will open opportunities for employment that is not directly related to the tourism sector.(3) For villages it will increase the source of village income. (4) infrastructure development. Suggestions that can be submitted for this study are: (1) Tourism management managers improve the quality of barcode scanners by bringing up a variety of tourist attractions offered on tourism objects, not just showing maps of tourist attractions.(2) The Department of Youth, Sports and Tourism disseminated to the community and young people in Janju Village to actively participate in the Tourism Awareness Group to improve the development of Colorful Village tourism objects.(3) The importance of the tourism sector to the regions makes the government aware of the importance of the sector, the government can support tourism sector activities by giving funds through the use of budget allocation funds.